Anton Chekov and his literary works as sources of studying humanism in medicine. - Semyonova, L. S.; Klimenko, I. N. (Medicni Perspektivi, 2018)
This article is devoted to a well-known doctor and writer A.P. Chekhov. It shows the influence of his doctor’s activity on the creative literary process and concept of humanism in his literary works.